2005
DOI: 10.1080/01902140500325023
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Lobe Dysfunction and False Memory Susceptibility in Older Adults

Abstract: The study reported here was conducted to examine the role of frontal lobe function in false memory susceptibility in older adults, as little research has specifically examined this question in older adults. False recognition was compared in three groups of older adults (one with no evidence of cognitive impairment, one with evident frontal impairment but no other dysfunction, and an Alzheimer's dementia group) to a single group of young adults. Results indicate that false memory susceptibility was highest in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Previous research has shown that the ability to remember in a category-based manner remains intact in older adults (e.g., Castel, 2005;Koutstaal, 2006;Koutstaal, Schacter, Gallucio, & Stofer, 1999;Reder et al, 1986), whereas on tests of precise recollection, older adults are more likely to accept as true false information that is similar to actually presented information (e.g., Aizpurua, Garcia-Bajos, & Migueles, 2009;Koutstaal, 2003;Koutstaal et al, 1999;Schacter, Koutstaal, Johnson, Gross, & Angell, 1997). This likelihood of false memory has been correlated with FLF not just in older adults (Butler, McDaniel, Dornburg, Price, & Roediger, 2004; see also LaVoie, Willoughby, & Faulkner, 2006), but also in younger adults (Chan & McDermott, 2007). In these studies, participants with relatively low-FLF level showed higher false-memory susceptibility than did high-FLF individuals.…”
Section: Frontal Lobe Functioningmentioning
confidence: 97%
“…Previous research has shown that the ability to remember in a category-based manner remains intact in older adults (e.g., Castel, 2005;Koutstaal, 2006;Koutstaal, Schacter, Gallucio, & Stofer, 1999;Reder et al, 1986), whereas on tests of precise recollection, older adults are more likely to accept as true false information that is similar to actually presented information (e.g., Aizpurua, Garcia-Bajos, & Migueles, 2009;Koutstaal, 2003;Koutstaal et al, 1999;Schacter, Koutstaal, Johnson, Gross, & Angell, 1997). This likelihood of false memory has been correlated with FLF not just in older adults (Butler, McDaniel, Dornburg, Price, & Roediger, 2004; see also LaVoie, Willoughby, & Faulkner, 2006), but also in younger adults (Chan & McDermott, 2007). In these studies, participants with relatively low-FLF level showed higher false-memory susceptibility than did high-FLF individuals.…”
Section: Frontal Lobe Functioningmentioning
confidence: 97%
“…Previous research has also found increased levels of false recognition in patients with damage to their frontal lobes (Lavoie, Wiloughby, & Faulkner, 2006; Parkin, Binschaedler, Harsent, & Metzler, 1996; Schacter, Curren, Galluccio, Milberg, & Bates, 1996), although there have been important exceptions to this pattern (Verfaellie, Rapcsak, Keane, & Alexander, 2004). This suggests that one possible explanation for the increase in false memories in patients with AD is the pathological changes not only to the hippocampal regions, but also to areas of the frontal cortex, with some researchers hypothesizing that inhibitory control may be especially important (Flanagan et al, 2012).…”
Section: Dysfunction Of Frontal Networkmentioning
confidence: 91%
“…False memories, the belief that items or events have been experienced before when they have not, occur across the lifespan, increase in normal aging, and are further exacerbated by neurocognitive disorders such as Alzheimer's disease (LaVoie, Willoughby, & Faulkner, 2005;Parkin, Bindschaedler, Harsent, & Metzler, 1996;Schacter, Curran, Galluccio, Milberg, & Bates, 1996). Whereas some false memories are innocuous, such as believing the groceries that you just bought are on the kitchen table when they are actually still in the car, others can be dangerous, such as thinking that you had turned off the stove when you had not.…”
Section: Introductionmentioning
confidence: 99%